Modification of caesarean section on the associations between air pollution and childhood asthma in seven Chinese cities. (December 2020) - Yu, Hongyao; Guo, Yuming; Zeng, Xiaoyun; Gao, Meng; Yang, Bo-Yi; Hu, Li-Wen; Yu, Yunjiang; Dong, Guang-Hui; ,; Zhou, Yang; Qian, Zhengmin; Sun, Jia; et al.
Abstract: It is unknown whether giving birth via caesarean section (c-section) is a modifier for the association between air pollution and asthma. From 2012 to 2013, 59, 754 children between the ages of 2 and 17 were randomly selected from 94 middle schools, elementary schools and kindergartens in seven Chinese cities for a cross-sectional study. The children's parents or guardians completed questionnaires, from which data on asthma as well as asthma-related symptoms were obtained. Participants' exposure to particles with an aerodynamic diameter ≤1.0 μm (PM1 ), ≤2.5 μm (PM2.5 ), and ≤10 μm (PM10 ) and exposure to nitrogen dioxide (NO2 ) were estimated using random forest models. We used mixed effects logistic regression models and added an interaction term between mode of delivery and ambient air pollution into the model to estimate effect modification from c-sections after appropriate adjustments for potential confounding variables. Among children delivered by c-section, the adjusted ORs for asthma and its symptoms per interquartile range (IQR) increase of PM1, PM2.5, PM10 and NO2 (1.20 95% CI: 1.07–1.34 to 2.04 95% CI: 1.87–2.24) were significantly higher than those of children delivered vaginally (1.05 95% CI: 0.92–1.19 to 1.33 95%CI: 1.21–1.47). The interactions between c-sections and ambient air pollution were statistically significant for all studied respiratory disorders, except current wheeze. Delivery via c-section may increase the risks of air pollution on asthma and its symptoms in Chinese children. Graphical abstract: Image 1 Highlights: Greater ambient air pollutant exposures were associated with higher odds of asthma. The associations were modified by a c-section birth among children and adolescents. The modifying effect of c-section on childhood asthma tended to be stronger among girls and older children. Abstract : The adverse respiratory effects of air pollution were significantly stronger among children delivered by caesarean section than among children delivered vaginally.